Dual blockade of IL-17A and IL-36 pathways via a bispecific antibody exhibits enhanced anti-inflammatory potency - Ma, Xiaojuan; Zhang, Shuang; Ren, Xiaochen; Feng, Yujie; Li, Hui; Chen, Shi; Xu, Jingen; Wang, Yanting; Peng, Guo-yuan; Yan, Qingran; Jia, Huifeng; Xia, Simin; et al. (Frontiers in Immunology, 2024)
Antibody drugs targeting single inflammatory cytokines have revolutionized the treatment of immune-mediated inflammatory diseases. To investigate whether dual targeting interleukin-17 (IL-17) and IL-36 enhances anti-inflammatory activity, bispecific Ab HB0043 was generated by linking the single chain fragment variables (scFvs) from humanized anti-IL-36R antibody (HB0034) to the C-terminus of the heavy chain of anti-IL-17A IgG1 (HB0017) Fc using a flexible peptide linker. HB0043 largely maintained the binding affinities and biological activities of the two parent monoclonal antibodies (mAbs) in vitro. IL-17 and IL-36 cooperated to amplify the expression of pro-inflammatory and pro-fibrotic genes in normal human dermal fibroblasts (NHDF). However, HB0043 more effectively blocked IL-6 and IL-8 production in NHDF stimulated by IL-17A and IL-36 compared to two monoclonal antibodies. In a mouse model of Oxazolone (OXA)-induced atopic dermatitis and Imiquimod (IMQ)-induced skin inflammation, administration of both anti-IL17A mAb HB0017 and anti-mouse IL-36R surrogate antibody HB0034SA showed improved effectiveness in alleviating skin thickening and inflammation based on histological assessment. Further, in cynomolgus monkeys, HB0043 showed no enhanced target-related toxicity compared with the two parental mAbs in vivo and with a moderate increase in production of anti-drug antibodies. Together, dual blockade of IL-17A and IL-36R in the form of a bispecific antibody may have advantages in blocking the overlapping and non-overlapping functions of these two cytokines in skin inflammation that could not optimally be curtailed with single mAbs. In conclusion, as monotherapy may reach therapeutic celling for certain difficult-to-treat inflammatory and fibrotic diseases, dual targeting could potentially pave a way to combat these diseases.